2015
DOI: 10.1179/1528433614z.0000000012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of concomitant medications in older HIV+ patients and comparison with general population

Abstract: Older HIV-positive patients frequently take a higher number of co-medication, which increases the risk of adverse events, interactions with other medication, and may lead to poorer treatment adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 21 publications
6
33
4
Order By: Relevance
“…The differences were statistically significant for males but not for females; this was probably because females were underrepresented in this HIV population. The findings of this study were consistent with previous findings by our group, which showed no differences between the percentage of HIV-positive males and males from the general population receiving cardiovascular drugs such as renin–angiotensin inhibitors or lipid-lowering drugs 23. In the present study, there were no differences in cardiovascular drug use between the two populations compared, independently of sex.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The differences were statistically significant for males but not for females; this was probably because females were underrepresented in this HIV population. The findings of this study were consistent with previous findings by our group, which showed no differences between the percentage of HIV-positive males and males from the general population receiving cardiovascular drugs such as renin–angiotensin inhibitors or lipid-lowering drugs 23. In the present study, there were no differences in cardiovascular drug use between the two populations compared, independently of sex.…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of HIV-positive patients who collected five or more non-ART medications in our study is slightly lower than previously reported rates (43.8% and 47.2% for males and females, respectively, in our study compared with 54.0% and 57.6% for both sexes in other studies) 17,23. This difference could be due to the fact that, unlike other studies, we did not include alternative treatments.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…70,[120][121][122][123] The clinician must face the challenge of selecting an appropriate HAART regimen in a na€ ıve HIV-infected elderly patient and to adapt an ongoing HAART according to concurrent medications in an aging patients already receiving antiretrovirals. Table 2 illustrate a brief summary of the most relevant interactions between first-line antiretrovirals and commonly prescribed drugs in the aging population.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%